Design of Waste Collection Sites at President University Campus: The Principles of Reduce, Reuse, Recycle (3R) - Stephanie, Inna (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Waste management is a critical issue in Indonesia, where most of the waste produced is still not separated for disposal and handled properly. Despite having separate waste bins, President University has not consistently implemented waste separation, making it an appropriate case study for designing a 3R-based Temporary Waste Storage Site. This study aims to calculate the volume of existing waste and design a user-friendly 3R Temporary Waste Storage Site that supports the principles of Reduce, Reuse, and Recycle on campus. This study uses a mixed methods approach, combining direct observation and measurement of waste volume in Buildings A and B for eight consecutive days in accordance with SNI 3964:2025, as well as a questionnaire survey to assess students perception, behaviors, norms, and responsibility regarding waste management. The results show that the average waste production on campus is 79.75 kg/day, dominated by inorganic waste such as plastic bottles (17.5%) and plastic food containers (16.6%), followed by paper, cardboard, and organic food waste. The proposed technical design includes separate organic, inorganic, and residual waste facilities, composting using bamboo aerators, and leachate reservoirs. This design meets Indonesian regulatory requirements, with increased sorting and processing capacity. Social analysis using multiple linear regression revealed that perception significantly influenced student responsibility in waste management (p = 0.001), while behavior and norms showed weaker effects.